Attention bias as a mediator of the association between interparental conflict and cortisol reactivity - Obstfeld, Maya, author; Lucas-Thompson, Rachel, advisor; Faw, Meara, committee member; Quirk, Kelley, committee member (Colorado State University. Libraries, 2021)
The current study aimed to explore whether attention bias mediated the relationship between adolescents' appraisals of interparental conflict (IPC) and cortisol reactivity (CR). There is a robust literature on the relationship between attention bias and anxiety in children and adults (Bar-Haim et al., 2007; Cisler & Koster, 2011), and an emerging literature on how interparental conflict is associated with an attention bias toward angry interactions (Lucas-Thompson et al., 2020). While there is a robust association in the literature between interparental conflict and cortisol reactivity (Davies et al., 2007; Lucas-Thompson, 2012; Koss et al., 2012), the results of this study found no association between the two variables. Similarly, the results of this study indicated no associations between attention bias and any other variables. The results of this study suggest that attention bias may be a moderator, or risk factor in the relationship between IPC and CR. Additionally, further research is needed to determine whether a conflict specific stressor should be used to elicit more variability in cortisol reactivity. Further research should continue to aim to link neurobiological processes to clinically relevant topics, as it is essential to bridge the gap between the medical field and the psychotherapy process.
Keywords: cortisol; interparental conflict; HPA axis; attention bias